Plessy v. Ferguson : race and inequality in Jim Crow America - Hoffer, Williamjames (Landmark law cases & American society., 2012)
"Six decades before Rosa Parks boarded her fateful bus, another traveler in the Deep South tried to strike a blow against racial discrimination--but ultimately fell short of that goal, leading to the Supreme Court's landmark 1896 decision in Plessy v. Ferguson. Now Williamjames Hull Hoffer vividly details the origins, litigation, opinions, and aftermath of this notorious case"--Provided by publisher.